2015
DOI: 10.1016/j.ijcha.2015.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Overweight predicts poorer exercise capacity in congenital heart disease patients

Abstract: BackgroundOverweight (OW) and obesity (OB) are endemic in the United States and affect adolescents and adults with congenital heart disease (ACHD). Defining the burden of excess weight on the cardiovascular system in ACHD is the goal of this study. Limitation of exercise capacity due to overweight or obesity might be reversible with weight loss and improve quality of life for ACHD adults.MethodsExercise tests performed using a Bruce protocol and measurement of maximum oxygen consumption were retrospectively re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Other study concluded obesity did not affect the mortality and short term outcomes with adult population, but there is an increase of renal impairment on obese severe congenital heart disease patient. 20 Patient with congenital heart disease have an increased risk for developing metabolic syndrome, and may be because of several risk factors including exercise restriction and differing nutritional strategies in infancy. 19,20 In our patient, the risk for metabolic syndrome is augmented by his obesity.…”
Section: Obesity In Congenital Heart Disease (Chd)mentioning
confidence: 99%
See 1 more Smart Citation
“…Other study concluded obesity did not affect the mortality and short term outcomes with adult population, but there is an increase of renal impairment on obese severe congenital heart disease patient. 20 Patient with congenital heart disease have an increased risk for developing metabolic syndrome, and may be because of several risk factors including exercise restriction and differing nutritional strategies in infancy. 19,20 In our patient, the risk for metabolic syndrome is augmented by his obesity.…”
Section: Obesity In Congenital Heart Disease (Chd)mentioning
confidence: 99%
“…20 Patient with congenital heart disease have an increased risk for developing metabolic syndrome, and may be because of several risk factors including exercise restriction and differing nutritional strategies in infancy. 19,20 In our patient, the risk for metabolic syndrome is augmented by his obesity. Obesity in congenital heart disease have also been seen to have lesser exercise time even with a milder disease severity.…”
Section: Obesity In Congenital Heart Disease (Chd)mentioning
confidence: 99%
“…For this reason SSG has frequently been used by researchers interested in studying the benefits of exercise for promoting health in older populations. For example, several studies have been performed to investigate the effect of SSG exercise on the physiology of older adults in community settings [10][11][12][13][14] and also patients with obesity [15], diabetes [16][17][18][19] and heart disease [20]. The particular effect of SSG on cognitive function in older subjects has also been investigated [21][22][23], although it would appear that the protocols used did not always fully and accurately incorporate all the customary elements.…”
Section: Introductionmentioning
confidence: 99%